2016
DOI: 10.3329/bjp.v11i2.26759
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear shuttling of Y Box binding protein-1, its clinical relevance in cancer and as a therapeutic target

Abstract: Y-box binding protein 1 (YB-1) is an imperative biomarker for the clinical outcome of cancer patients. An overexpression of YB-1 in cancerous and adjoining tissues is an indication of aggressiveness and advanced stages. In normal resting cells, YB-1 is localized in cytoplasm while in stress conditions like cancer, nuclear shuttling of YB-1 takes place. In this review, the clinical importance of YB-1 in different cancers and the mechanism behind YB-1 nuclear shuttling have been discussed in detail. Targeted che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 152 publications
(217 reference statements)
0
1
0
Order By: Relevance
“…YBX1 is a 36 kD protein composed of an N-terminal alanine/proline-rich domain (A/PD), a C-terminal domain (CTD), as well as a CSD (Fig 3A) (Lyabin et al, 2014). The CSD region is similar to cold shock proteins found in bacteria with respect to its tertiary structure (Kloks et al, 2002), whereas the A/PD and CTD regions are thought to lack any intrinsic structure (Kloks et al, 2002;Gunasekaran et al, 2016). The TriFC results showed that all three YBX1 domains could interact with HOTAIR (Fig 3B).…”
Section: A Novel Irfp-trifc System For Investigating Lncrna-protein Interactionsmentioning
confidence: 99%
“…YBX1 is a 36 kD protein composed of an N-terminal alanine/proline-rich domain (A/PD), a C-terminal domain (CTD), as well as a CSD (Fig 3A) (Lyabin et al, 2014). The CSD region is similar to cold shock proteins found in bacteria with respect to its tertiary structure (Kloks et al, 2002), whereas the A/PD and CTD regions are thought to lack any intrinsic structure (Kloks et al, 2002;Gunasekaran et al, 2016). The TriFC results showed that all three YBX1 domains could interact with HOTAIR (Fig 3B).…”
Section: A Novel Irfp-trifc System For Investigating Lncrna-protein Interactionsmentioning
confidence: 99%